The Economic Sanctions Channel For The Curse Of The Petro-State Of Iran: Evidence From The Synthetic Control Method - Malik Cahyadin; Basem Ertimi; Tamat Sarmidi (Universitas Udayana, 2024)
This study estimates the impact of economic sanctions on oil exports and economicgrowth in the case study of Iran. By creating a synthetic control group method thatreproduces the oil exports and economic growth before economic sanctions areimposed in the case of Iran, we compare the oil exports as well as the economic growthof the Synthetic and the actual for each period. Using the synthetic control method,we fill a major gap in the sanctioned literature in the petrostate economies case study.Our study finds that both oil exports and the economic growth of Iran would havebeen lower had it not been exposed to economic sanctions. This research is embeddedin the comparative and international landscape linked to the relations of internationalinfluences with the domestic economy. The findings explain that economic sanctionsare a leading factor in the variations in oil exports and economic growth, which canbe reflected in the oil curse. We claim that our empirical investigation can contributeto policy formulation in the domestic and foreign arena by sanctioned countries.Overall, the findings confirm that the imposition of sanctions on a petrostate economylike (Iran) can be operated as another channel of the resource curse from internationaland foreign policy perspectives.